A Landscape-Level Assessment of Restoration Resource Allocation for the Eastern Monarch Butterfly - Solis-Sosa, Rodrigo; Mooers, Arne Ø.; Larrivée, Maxim; Cox, Sean; Semeniuk, Christina A. D. (Frontiers in Environmental Science, 2021)
The long-distance migration of the eastern Monarch butterfly (Danaus plexippus) is in decline primarily due to habitat loss. Current habitat restoration programs focus on re-establishing milkweed, the monarch larvae' primary food source, in the central United States of America. However, individual components of the monarch life cycle function as part of an integrated whole. Here we develop the MOBU-SDM, a migration-wide systems dynamics model of the Monarch butterfly migratory cycle to explore management strategies' impacts. Our model offers several advances over previous efforts, considering complex variables such as dynamic temperature-dependent developmental times, dynamic habitat availability, and weather-related mortality across the entire range. We first explored whether the predominant focus of milkweed restoration in the mid-range of the monarch’s migration could be overestimating the Monarch's actual habitat requirements. Second, we examined the robustness of using the recommended 1.2-1.6 billion milkweed stems as a policy objective when accounting for factors such as droughts, changes in temperature, and the stems’ effective usability by the Monarchs. Third, we used the model to estimate the number and distribution of stems across the northern, central, and southern regions of the breeding range needed to reach a self-sustainable long-term Monarch population of 6 overwintering hectares. Our analysis revealed that concentrating milkweed growth in the central region increases the size of the overwintering colonies more so than equivalent growth in the south region, with growth in the northern region having a negligible effect. However, even though simulating an increase in milkweed stems in the south did not play a key role in increasing the size of the overwintering colonies, it plays a paramount role in keeping the population above a critically small size. Abiotic factors considerably influenced the actual number of stems needed, but, in general, our estimates of required stems were 43%-91% larger than the stems currently set as a restoration target: our optimal allocation efforts were 7.35%, 92%, and 0.15% to the south, central, and northern regions, respectively. The MOBU-SDM provided us with new avenues to investigate the butterfly migration as a complex biological system and contribute to more robust restoration policies for this unique species.